Practising an Anti-Colonial Citizenship Education Through a Blended Learning Course on Aboriginal Law - Robertson, Sean (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2021)
In the wake of the Truth and Reconciliation Commission, Indigenous peoples and non-Indigenous Canadians find themselves aspiring towards transitional justice. Yet they do so with a democracy in need of some repair. One prime site for fostering democratic renewal – the post-secondary sector – is under pressure from corporatization and political forces working to narrow freedom of expression and academic freedom. This sector, however, continues to offer some hope through liberal, anti-oppressive, anti-colonial, and Indigenous pedagogies that promote a public ethical responsibility beyond the self. Yet encouraging these pedagogies is not straightforward, including for those teaching courses such as Aboriginal law in a blended learning format. In the context of the spread of online education and the dearth of scholarship on anti-oppressive pedagogies therein, on the one hand, and the reluctance of legal educators to adopt anti-colonial pedagogies, on the other, there is an urgency to build knowledge about how to develop citizenship education. Anti-colonial citizenship education includes content about the establishment of settler society and the status of Indigenous nations. Furthermore, it is operationalized through active learning practices. Based on Indigenous and non-Indigenous pedagogical theories, these practices are argued to support a tripartite “intellectual framework” comprised of critical thinking, collaboration, and self-directed learning. Through a case study of an undergraduate course, the argument is made for the efficacy of a number of active learning practices to produce this intellectual framework. It is suggested that, in addition to better learning outcomes, an anti-colonial citizenship education is materialized insofar as the intellectual framework inspires a sensibility for complexity and independent thinking, “civic culture,” and autonomous inquiry and openness to alternative epistemologies.